Study of Seismic Performance of Chinese-Style Single-Layer Suspended Ceiling System by Shaking Table Tests - Huanjun Jiang; Yong Wang; Liusheng He (Advances in Civil Engineering)
During some recent earthquakes, the suspended ceiling system (SCS) in buildings suffered severe damage. The seismic performance of SCS attracted more attention from researchers. In this study, full-scale shaking table tests on two Chinese-style single-layer SCSs with different boundary conditions are conducted. The seismic damage and earthquake responses, including acceleration, displacement, and strain responses, are compared. The effect of the boundary condition on the seismic performance of the SCS is studied. It is found that the seismic performance of the SCS is significantly affected by the boundary condition. Compared with the SCS with the free condition at the boundary, the damage to the SCS installed with seismic clips at the boundary is much slighter. Compared with the SCS with the free condition, the median of acceleration amplification factor (AAF), the peak displacement (PD), and maximum strain of the SCS installed with seismic clips are reduced by up to 63%, 99%, and 84%, respectively. At the end of the tests, the SCS with the free condition at the boundary completely collapsed with 68% of the panels falling, while only 15% of panels fell in the SCS installed with seismic clips. The seismic clips could avoid the falling of the grids from the peripheral support and ensure the integrity of the SCS. With the help of seismic clips installed at the boundary, the responses of the ceiling, such as acceleration, displacement, and strain, decrease significantly, and thereof, the collapse resistance capacity is improved.